Foreign exchange regime, the real exchange rate and current account sustainability: The case of Turkey - Sübidey Togan; Hasan Ersel (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
During the last two and half decades Turkey has suffered from three foreign exchange crisis resulting in considerable loss of income. The paper argues that the country in order to avoid the foreign exchange crisis has to stay away from having too big current account deficits. Noting that under perfect capital mobility there will always be the unavoidable risk of speculative attacks on the currency unless the country resolves its fiscal problems, attains price stability, and achieves a sound banking sector, the paper stresses importance of current account sustainability and highlights shortcomings of current policies pursued by Turkey.
Keywords: F31; F41; 330; Current account sustainability; Turkey